Evolution of Parasitoidism in Hymenoptera - Sevda Hastaoğlu Örgen; Mehmet Gülmez (Turkish Journal of Agriculture: Food Science and Technology)
Insects, the most diverse group of animals, are known to benefit society for a sustainable future. By focusing on the use of natural enemies of pests, including parasitoids and predators, the need for biological pest control for the conservation of agricultural crops has been emphasized. Parasites are organisms that live in the body of another organism and feed on it without killing it, while predators hunt, kill and eat their prey. Parasitoids, on the other hand, live in or on another organism and feed on it, ultimately killing the host. Our study highlights the use of parasitoids to control pests in agriculture and describes the parasitoid lifestyle as an evolutionary transition between parasitism and predation. It also notes that parasitoid larvae typically require only one host to complete their development and can be used to control a wide range of pests. The aim of this study was to determine the origin of the parasitic life form of order Hymenpotera, the mechanisms revealed by the parasitic life form, the importance of life strategies, the types of parasitism and to evaluate the important insect groups belonging to the order Hymenoptera used in biological control.